Comparison of Patient and Proxy Assessment of Patient-Centeredness in the Care of Coronary Heart Disease: A Cross Sectional Survey Using the PACIC-S11.1. (November 2020) - Vennedey, Vera; Peltzer, Samia; Shukri, Arim; Müller, Hendrik; Jessen, Frank; Albus, Christian; Stock, Stephanie
Introduction: When making medical care more patient-centered, surveys on patients' and their relatives' experiences can be helpful in identifying opportunities for improvement. In cases where the targeted patients are unable to express their own perspective, for example, due to them being too young or suffering from severe impairments, proxies can serve as substitutes. Proxies are frequently used in care planning and consent. Nevertheless, it is unclear whether patients' assessments of how patient-centered their medical care is are similar to those of their proxies. This study aims to assess the level of consistency between patients' and their proxies' assessments using an adapted version of the Patient Assessment of Chronic Illness Care (PACIC) short form questionnaire. Methods: In a cross-sectional study, patients with coronary heart disease were recruited at cardiologists' offices, rehabilitation clinics and hospitals. Participants were surveyed with regard to the perceived level of patient-centeredness during their care using an adapted version of the German PACIC short form (PACIC-S11.1). Correlations in the assessments made by each patient and their respective proxy were analyzed. On the level of the patients group and the relatives group differences between mean ratings for each item were compared using paired t -tests. Results: In total, 74 pairs of patients and proxies submitted the completed questionnaire. On the level of the individual patient/proxy pairs, no correlation, or significant but low correlation, was found between the ratings. On the group level, patients' and their proxies' item ratings were similar in the interpretation of averages, but still demonstrated statistically significant differences. Overall, patients rated their care as more patient-centered than their proxies did. Conclusion: The study shows that, on the individual level, proxies' ratings do not necessarily reflect the patients' assessment of PCC. On the group level, the assessments of relatives regarding PCC are similar to those of the patients. Trial registration: German clinical trials register (Deutsches Register Klinischer Studien, DRKS) Registration Number: DRKS00012434 (URL:https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00012434 )